Nasopalatine Ducts and Flehmen Behavior in the Mandrill: Reevaluating Olfactory Communication in Old World Primates. Issue 7 (22nd March 2013) - CHARPENTIER, MARIE J.E.; MBOUMBA, SYLVÈRE; DITSOGA, CLAUDE; DREA, CHRISTINE M.; Higham, James P.; Semple, Stuart
Abstract Compared to other modes of communication, chemical signaling between conspecifics generally has been overlooked in Old World primates, despite the presence in this group of secretory glands and scent‐marking behavior, as well as the confirmed production and perception of olfactory signals. In other mammalian species, flehmen is a behavior thought to transport primarily nonvolatile, aqueous‐soluble odorants via specialized ducts to the vomeronasal organ (VNO). By contrast, Old World primates are traditionally thought to lack a functional VNO, relying instead on the main olfactory system to process volatile odorants from their environment. Here, in the mandrill (Mandrillus sphinx), we document unusual morphological and behavioral traits that typically are associated with the uptake of conspecific chemical cues for processing by an accessory olfactory system. Notably, we confirmed that both sexes possess open nasopalatine ducts and, in response to the presentation of conspecific odorants, we found that both sexes showed stereotyped behavior consistent with the flehmen response. If, as in other species, flehmen in the mandrill serves to mediate social or reproductive information, we expected its occurrence to vary with characteristics of either the signaler or receiver. Flehmen, particularly in a given male, occurred most often in response to odorants derived from male, as opposed to female, conspecifics. Moreover, odorants derived during the breeding season elicited more flehmen responses than did odorants collected during the birthing season. Lastly, odorants from reproductively cycling females also elicited more responses than did odorants from contracepted females. Although confirming a link between the nasopalatine ducts, flehmen behavior, and olfactory processing in mandrills would require further study, our observations provide new information to suggest anatomical variability within Old World primates, calling further attention to the underappreciated role of chemical communication in this lineage. Am. J. Primatol. 75:703‐714, 2013. © 2013 Wiley Periodicals, Inc.